An XSA based assessment of beaked redfish (S. mentella and S. fasciatus) in NAFO division 3M - Ávila de Melo, A.; Saborido-Rey, Fran; Alpoim, R. (Northwest Atlantic Fisheries Organization, 2007)
43 páginas, 11 tablas, 8 figuras.-- Scientific Council Meeting The 3M beaked redfish stock is regarded as a management unit composed of two populations from two very similar species (Sebastes mentella and Sebastes fasciatus). In June 2003 a new Spanish research vessel, the RV Vizconde de Eza (VE) replaced the RV Cornide de Saavedra (CS) that had carried out so far the EU survey series. In order to preserve the full use of the 1988-2002 survey indices available for beaked redfish, the original time series were converted to the new RV units. An Extended Survivor Analysis (Shepherd, 1999) was performed using the previous XSA framework and the revised EU survey abundance’s at age as the tuning input file. Very high fishing mortalities until 1996 forced a rapid and steep decline of abundance, biomass and female spawning biomass of the 3M beaked redfish stock. With low fishing mortalities since then the stock decline was halted and the survival and growth of the existing cohorts allowed a discrete but continuous growth of 4+ biomass and female SSB from 1998 onwards. Meanwhile the income of a sequence of weak year classes (1991-1997) kept the 4+ abundance stable at a low level till 2001. However on the most recent years (2003-2006) a sequence of above average year classes from 1998 to 2002, each one greater than the previous, recruit each year to the 4+ stock, pumping abundance and biomass at the beginning of 2006 to a maximum and a second high of the 1989-2006 interval, respectively. At the same time the stock reproductive potential has increase substantially and above average year classes are being generated by parental female stock with biomass sizes well bellow the ones that produced the previous abundant 1989-1990 cohorts. Nevertheless these results of the present XSA assessment don’t change the perception of previous assessments, that this is still an unbalanced stock strongly leaning to the younger age groups and that female spawning stock biomass should be allowed to recover to the former 1989-1990 level, in ...